(untitled) (Research, Society and Development, 2021)
Introduction: The banana originates from the Far East and due to the requirement of heat for its development to be done properly, it is a typical plant in places with tropical climates. Due to the high level of carbohydrates present in its composition, it is considered an excellent food source of energy, in addition, when still green, its levels of minerals such as: potassium, manganese, iodine and zinc are higher than in its state matured. Due to the presence of a starch called, “resistant starch”, the green banana has functional properties similar to dietary fibers, thus helping to prevent degenerative diseases associated with intestinal metabolism. General Objective: In order to describe the benefits of using green pacovan banana as a great functional food for the human body. Methodology: A literature search was carried out, with the aim of identifying the nutritional composition and characterizing the effects of resistant starch. Result and Discussion: Describe the effects of using green bananas as a functional food, highlight the importance of using green bananas in prevention and treatment of chronic diseases and elucidate the importance of nutritional education regarding knowledge about new food alternatives. Conclusion: It was found that the green banana has several benefits, being a functional food of low cost for the population. Among the ways to use them, it can be transformed into biomass.